THE EFFECT OF ADOBE FLASH BASED INTERACTIVE MEDIA ON THE PGSD STUDENTS’ LISTENING ABILITY AT THE FACULTY OF TEACHER TRAINING AND EDUCATION UNIVERSITAS RIAU - Nabilah Anandri Dalhayat; Otang Kurniaman; Elvrin Septyanti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to determine the effect of adobe flash based interactive media on the PGSD students’ listening ability at FKIP Universitas Riau. This study involved 38 students consisting of 36 female students and 2 male students. The method in this study was pre-experimental design with one group pretest-posttest design. The instrument to collect the data was a test consisting of 50 questions both in pretest and posttest. Then, the data were analyzed by using descriptive statistical techniques. The results showed that there was adobe flash based interactive media had no effect on the students’ listening ability at FKIP Universitas Riau.